Understanding The Interaction Between Pressure and Volume in Gas Systems Through Boyle’s Law Practicum - Febrianti, Widi; Hendriansyah, Egi; Imani, Kaida Azra; Harielpaniadi, M. Addya; Sari, Nuraeni Nanda; Hartini, Tri Isti (Program Studi Tadris IPA, Fakultas Tarbiyah (IAIN) Kediri, Indonesia, 2024)
This research aims to understand the interaction between pressure and volume in gas systems, as explained by Boyle’s Law, has significant applications in industrial and medical fields. This study examines the relationship between pressure and volume through practical experiments using constant piston height. Measurements were carried out to validate the inverse proportionality between pressure and volume under constant temperature conditions. The findings revealed a consistent increase in pressure across three experiments, with average values of 100.84 Pa, 100.87 Pa, and 100.88 Pa, respectively. These results demonstrate the applicability of Boyle’s Law in understanding gas behavior and optimizing gas-based systems. This research contributes to practical applications such as medical ventilators and gas cylinder designs, offering insights for technological innovation in these areas.